2015
DOI: 10.1590/1807-1929/agriambi.v19n11p1021-1027
|View full text |Cite
|
Sign up to set email alerts
|

Water infiltration rate in Yellow Latosol under different soil management systems

Abstract: A B S T R A C TThe management systems affect soil structure, causing changes in porosity that can influence soil water infiltration. In order to study the water infiltration rate in a Yellow Latosol under different tillage systems and different mathematical models, an experiment was conducted from October to December 2012, at the Center for Agricultural Sciences at the Federal University of Alagoas, using a randomized block design with five replicates, in a split-plot scheme. In the plots, the management syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
8
2
4
Order By: Relevance
“…Soil losses due to erosion, reduction of organic matter, compaction, reduction of porosity, and permeability, are some of the consequences of poor use of the soil resource. This investigation disagreed with the results found by other authors (Cunha et al 2015;Kamimura et al 2009;Pinheiro et al 2009) when they studied the infiltration rates in different soil management systems (conventional, minimal and no-tillage), they concluded that minimal cultivation provided higher values of soil water infiltration rate. This difference can often be associated with different soil classes, contribution of organic matter, soil quality, different climate and the time of use in the areas.…”
Section: Resultscontrasting
confidence: 99%
“…Soil losses due to erosion, reduction of organic matter, compaction, reduction of porosity, and permeability, are some of the consequences of poor use of the soil resource. This investigation disagreed with the results found by other authors (Cunha et al 2015;Kamimura et al 2009;Pinheiro et al 2009) when they studied the infiltration rates in different soil management systems (conventional, minimal and no-tillage), they concluded that minimal cultivation provided higher values of soil water infiltration rate. This difference can often be associated with different soil classes, contribution of organic matter, soil quality, different climate and the time of use in the areas.…”
Section: Resultscontrasting
confidence: 99%
“…Puddling and other tillage practices obliterated pore connectivity, and lower aggregate stability caused clogging of pores during infiltration (Kukal & Aggarwal, 2002). There have been contrasting reports of higher infiltration rates (e.g., Das et al, 2018 (due to better pore connectivity) and Thierfelder & Wall, 2010 (due to residue retention and better aggregation)), lower infiltration rates (e.g., Liu, Zhang, Kravchenko, & Iqbal, 2015 (due to the lower amount of macropores in clay textured soil)) or no change (Cunha et al, 2015;Singh, Phogat, Dahiya, & Batra, 2014) in the infiltration rate through adoption of no-tillage or reduced tillage. A global metanalysis concluded there was higher soil infiltration rate with longer duration of adoption of no-tillage (Mondal, Chakraborty, Bandyopadhyay, & Aggarwal, 2019a,b).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the mathematical adjustments, it can be observed that the model that best adjusted the BIV was the one of Horton, that in all the managements obtained the result equal to the one obtained in the field. Cunha et al (2015), where the methodologies of Kostiakov, Kostiakov-Lews and Horton were also used.…”
Section: Resultsmentioning
confidence: 99%
“…I -estimated instantaneous infltration rate, mm h-1; residual mass ratio (RMR), adjustment coefficient (AC) and efficiency (EF) as described by CUNHA et al (2015).…”
Section: Modelo De Kostiakovmentioning
confidence: 99%